The mitigative effect of isorhamnetin against type 2 diabetes via gut microbiota regulation in mice - Li, Jinjun; Yuan, Huimin; Zhao, Zhiqi; Li, Li; Li, Xiaoqiong; Zhu, Liying; Wang, Xin; Sun, Ping; Xiao, Yinping (Frontiers in Nutrition, 2022)
In order to demonstrate the effects of isorhamnetin (IH) on the symptoms of Type 2 diabetes mellitus (T2DM) and the role of gut microbiota in this process, an T2DM mouse model was established via a high-fat diet and streptozotocin. After six weeks of IH intervention and diabetes phenotype monitoring, the mice were dissected. We detected blood indicators and visceral pathology. Contents of the cecum were collected for 16S rRNA sequencing and short chain fatty acid (SCFAs) detection. The results showed that after IH intervention, the body weight of type 2 diabetic mice was gradually stabilized, fasting blood glucose was significantly decreased, and food intake was reduced (P<0.05). Isorhamnetin significantly increased the level of SCFAs and decreased the levels of blood lipids and inflammatory factors in mice (P<0.05). 16S rRNA sequencing results showed that Lactobacillus were significantly decreased and Bacteroidales S24-7 group_norank were significantly increased (P<0.05). Interestingly, gut microbiota was significantly correlated with inflammatory factors, blood lipids, and SCFAs (P<0.05). Taken together, our data demonstrated that isorhamnetin could improve the diabetic effects in T2DM mice, which might be mediated by gut microbiota.